Symptoms characteristics of personality disorders associated with suicidal ideation and behaviors in a clinical sample of adolescents with a depressive disorder - Gifuni, Anthony Joseph; Spodenkiewicz, Michel; Laurent, Geneviève; MacNeil, Sasha; Jollant, Fabrice; Renaud, Johanne (Frontiers in Psychiatry, 2023)
Pathological personality traits have repeatedly been identified as important risk factors for suicidal ideation and behaviors. Moreover, impulsive-aggressive traits, have shown a consistent association with suicidal behaviors across the lifespan. Adolescence represents a critical period for the emergence of different personality traits, mood disorders, and suicidal behaviors, but the relationship between these variables remain poorly understood. These variables were examined in a cross-sectional case-control design involving three groups: 30 adolescents with a depressive disorder and past suicide attempt (Mean Age=16.2, Females=26), 38 adolescents with a depressive disorder but without past suicide attempt (Mean age=16.0, Females=29), and 34 healthy adolescent controls (Mean age=15.2, Females=22). Suicidal ideations were indexed using Suicidal Behavior Questionnaire (SBQ-R), psychiatric disorder assessed using a semi-structured questionnaire (K-SADS-PL), depressive symptoms with the Beck Depressive Inventory (BDI), personality traits with the Scheduled Clinical Interview for the DSM-IV (SCID-II) screening questionnaire, and impulsivity with the Barratt Impulsivesness Scale (BIS). Findings showed that impulsivity (F=11.0, p<0.0001) and antisocial personality traits (p<0.001, d=0.70) displayed the most robust association with adolescent suicide attempts. Borderline personality traits did not discriminate attempters from non-attempters but presented high correlations with suicidal ideation and depression severity. In an item-wise analysis, suicide attempt status was uniquely correlated with antisocial personality traits. Suicide attempt status also correlated with non-suicidal self-injury and chronic feelings of emptiness. The caveats of this cross-sectional study include the stability of personality traits in adolescence and the limited sample size. In sum, suicidal behaviors were characteristically correlated with increased impulsivity and antisocial personality traits, but other personality traits were relevant to adolescent depression and suicidal ideation. Understanding the emergence of personality traits and suicidal behaviors in a developmental context can ultimately inform not only the neurobiological origin of suicidal behaviors, but also provide new avenues for early detection and intervention.